Biomarkers in Human Anaphylaxis: A Critical Appraisal of Current Evidence and Perspectives - Beck, Sarah C.; Wilding, Thomas; Buka, Richard J.; Baretto, Richard L.; Huissoon, Aarnoud P.; Krishna, Mamidipudi T. (Frontiers in Immunology, 2019)
Anaphylaxis is a type I hypersensitivity reaction that is potentially fatal if not promptly treated. It is a clinical diagnosis, although measurement of serial serum total mast cell tryptase (MCT) is gold standard and may help differentiate anaphylaxis from its mimics. The performance characteristics of MCT assays in anaphylaxis has been variable in previous studies, due to multiple factors including differences in the definition of anaphylaxis, methods of MCT interpretation, clinical setting of anaphylaxis, causative agents, and timing of blood sample. An international consensus equation for MCT to interpret mast cell activation has been proposed and recently validated in the context of peri-operative anaphylaxis during general anaesthesia. There has been an interest in the detection of newer biomarkers in anaphylaxis including platelet activation factor (PAF), chymase, carboxypeptidase A3, dipeptidyl peptidase I (DPPI), basogranulin and CCL-2. The key determinants of an ideal biomarker in anaphylaxis are half-life, sample handling and processing requirements and cost. There may be a role for metabolomics and systems biology in the exploration of novel biomarkers in anaphylaxis. Future studies applying these approaches might provide greater insight into factors determining severity, clinical risk stratification, identification of mast cell disorders and improving our understanding of this relatively complex acute immunological condition. Post mortem MCT evaluation is used in Forensic Medicine during autopsy for cases involving sudden death or suspected anaphylaxis. Interpretation of post mortem MCT is challenging since there is limited published evidence and the test is confounded by multiple variables largely linked to putrefaction and site of sampling. Thus, there is no international consensus on a reference range. In this state of the art review, we will focus on the practical challenges in the laboratory diagnosis of anaphylaxis and critically appraise (a) performance characteristics of MCT in anaphylaxis in different clinical scenarios (b) the role for novel biomarkers and (c) post mortem MCT and its role in fatal anaphylaxis.